"Muda rápido!": Marcas da evolução da Língua Portuguesa no ciberjornalismo - Zamith, Fernando (2017)
The Portuguese language has registered in the last decades many changes originating from orality, which, more or less quickly, are moving to the written record of literature, journalism and law. One of the quickest and perhaps most surprising changes is the use of adverbial adjectives as "rápido" instead of "rapidamente". The purpose of this paper is to present the results of a pilot study on some grammatical changes of this type assimilated by online journalism, seeking further differences between European Portuguese and Brazilian Portuguese in relation to the linguistic aspects that we will be dealing with. As a general conclusion, we can claim that online journalism reproduces and adopts some linguistic changes disseminated by orality, but not with the extent that was expected. In 72 percent of the cases analyzed in Portuguese online media, the adverb "rapidamente" still prevails, but in Brazilian online media is already minority (41%). It was also possible to detect 15 percent of the occurrences of the phrase "se bem que" indicative and not conjunctive, in all cases with the concessionary sentence after the principal. Regarding the use of "embora", we conclude that in 100% of the cases the regency remains conjunctive and that in 74% of occurrences the conjunction arises after the sentence that should be the main one. The methodology used did not, however, allow to draw conclusions concerning the adverbial use of the adjectives "péssimo" and "ótimo", so further investigation should include a deeper data collection.